Preparation method of surface modified halloysite-oyster micro powder

Through the mixed calcination and surface modification treatment of elosteite-oyster powder, the problems of high production cost and insufficient adsorption performance of shell powder are solved, and efficient adsorption and biocompatibility are achieved, and suitable for environmental restoration and biomaterial fields.

CN120393939APending Publication Date: 2025-08-01NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510529132.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing shell powder has high production costs and limited room for improvement in adsorption performance, especially during the calcination process, low reaction activity, low calcium oxide conversion, low porosity, small specific surface area and pore volume.

Method used

The crystal structure transformation and surface modification treatment were controlled to form a porous structure by mixing the elolite powder and oyster shell powder, and then calcining with MgO in an alkaline solution, and then activated in an alkaline solution and reacting with L-lysine aqueous solution.

Benefits of technology

It significantly improves the adsorption performance of the product, increases the porosity and specific surface area, improves the adsorption capacity and biocompatibility of the material, and has antibacterial and deodorizing effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120393939A_ABST
    Figure CN120393939A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of surface modified halloysite-oyster micro powder, and belongs to the technical field of adsorption materials. The preparation method of the surface modified halloysite-oyster micro powder comprises the following steps: mixing halloysite powder and oyster shell powder to obtain mixed powder; mixing the mixed powder with MgO in an alkaline solution 1, carrying out fluxing modification to obtain pretreated powder, and calcining to obtain calcined powder; and putting the calcined powder into an alkaline solution 2, activating, then putting into an L-lysine aqueous solution, and reacting to obtain the halloysite-oyster micro powder. According to the invention, the problems of low reaction activity, low calcium oxide conversion rate, low porosity, small specific surface area and small pore volume in the calcination process of the oyster shell powder are solved, and the adsorption performance of the product is greatly improved. The problem of biocompatibility of the oyster micro-powder in application is solved through control and surface modification treatment of crystal configuration transformation of the oyster micro-powder in the calcining process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorption materials, and particularly to a preparation method of surface-modified halloysite-oyster micropowder. Background Art

[0002] Shell powder is a powder obtained by crushing and processing the shells of mollusks. The main component of shell powder is calcium carbonate, and it also contains substances such as calcium oxide, calcium hydroxide, chitin, amino acids, and polysaccharide substances, and can be applied to various fields. Shell powder has a porous fibrous double helix structure, which increases its surface area, thereby improving its adsorption capacity. Moreover, the fine particles of activated shell powder can enhance this property and can more effectively remove harmful substances such as free formaldehyde, benzene, ammonia, and odor substances in the air.

[0003] However, the existing production and processing process of shell powder is relatively complex, requires specific technologies and processes, and has a high production cost. Moreover, there is still room for improvement in the adsorption performance of existing modified shell powder, and it is urgent for those skilled in the art to conduct further research. Summary of the Invention

[0004] The purpose of the present invention is to provide a preparation method of surface-modified halloysite-oyster micropowder to solve the above problems in the background art. The present invention solves the problems of low reaction activity, low calcium oxide conversion rate, low porosity, small specific surface area, and small pore volume during the calcination process of oyster shell powder, and greatly improves the adsorption performance of the product. By controlling the crystal configuration transformation of oyster micropowder during the calcination process and surface modification treatment, the biocompatibility problem in its application is solved.

[0005] To achieve the above purpose, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention: Provide a preparation method of surface-modified halloysite-oyster micropowder, including the following steps:

[0007] Mix halloysite powder and oyster shell powder to obtain a mixed powder;

[0008] Mix the mixed powder with MgO in alkaline solution 1 to obtain an intermediate product, perform flux modification to obtain a pretreated powder, and calcine to obtain a calcined powder;

[0009] Place the calcined powder in alkaline solution 2 for activation, and then place it in an L-lysine aqueous solution for reaction to obtain halloysite-oyster micropowder.

[0010] Preferably, the halloysite powder is halloysite powder crushed to pass through a 30-mesh sieve, and the oyster shell powder is oyster shell powder crushed to pass through a 50-mesh sieve.

[0011] Preferably, the mass ratio of halloysite powder to oyster shell powder is 1:3.

[0012] Preferably, the pH value of the alkaline solution 1 is 12.4 - 12.6; the addition amount of MgO is 10 wt% of the intermediate product; the time of fluxing modification is 8 h.

[0013] Alkali treatment can remove impurities and organic matter on the surface of oyster shell powder, exposing more active sites, which helps to promote the decomposition of calcium carbonate in oyster shell powder during subsequent high-temperature calcination.

[0014] Preferably, the temperature of the calcination is 900 °C and the time is 1 h; the atmosphere of the calcination is nitrogen atmosphere and the nitrogen flow rate is 500 mL / min.

[0015] Preferably, the pH value of the alkaline solution 2 is 12.8 - 13.2; the temperature of the activation is 160 - 200 °C and the time is 24 - 28 h.

[0016] Through the activation of the alkaline solution 2, part of the soluble organic matter in the oyster shell powder can be removed, forming a more porous structure. At the same time, the activation of the alkali metal salt solution can increase the hydrophilicity of the oyster shell powder surface, which helps to improve its stability and adsorption capacity in the water environment.

[0017] Preferably, the concentration of the L-lysine aqueous solution is 10 - 15 wt%; the time of the reaction is 1 - 2 h, the reaction is carried out under ultrasonic conditions, and the frequency of the ultrasonic is 40 kHz.

[0018] The second technical solution of the present invention: Provide a surface-modified halloysite-oyster micropowder obtained according to the above preparation method.

[0019] The third technical solution of the present invention: Provide an application of the above surface-modified halloysite-oyster micropowder in the field of adsorption materials.

[0020] The technical principle of the present invention is as follows:

[0021] Oyster shell powder is mainly composed of calcium carbonate. After calcination treatment, the calcium carbonate therein will decompose into calcium oxide (CaO), which increases the adsorption capacity and reaction activity of the material. During the calcination process of oyster shell powder, its pore structure increases, providing more adsorption sites and enhancing its adsorption effect.

[0022] Halloysite is a natural clay mineral with a main component of silicate, having good adsorption and ion exchange properties. During the calcination process of the present invention, the SiO2 component in halloysite helps to reduce the reaction enthalpy and pyrolysis energy of calcium carbonate during calcination, helps to save energy consumption in the sample preparation process and promotes the decomposition of calcium carbonate in oyster shell powder to generate other products such as calcium oxide (CaO) and carbon dioxide, thereby promoting the formation of pore structure, thereby increasing the specific surface area and porosity of oyster shell powder and achieving the technical effect of enhancing the adsorption capacity of the product. At the same time, the addition of halloysite promotes the microstructure reorganization of oyster shell powder during calcination, generates more pores and cracks, improves the porosity of the material, and helps to increase the pore volume and pore diameter of the material.

[0023] MgO as a flux in the present invention can reduce the decomposition temperature of calcium carbonate, promote the chemical reaction during calcination, make CaCO3 more easily converted into calcium oxide, further increase the adsorption capacity and reaction activity of the material, improve the adsorption efficiency of the material, and reduce the production cost. The addition of MgO improves the pore structure of oyster shell powder during calcination, increases the specific surface area and pore volume of the material, and provides more active sites for adsorption.

[0024] Experiments found that the surface microstructure of oyster shell powder began to change at a calcination temperature of 700-800 °C, changing from a planar shape to a flocculent shape, and with the further increase of the calcination temperature, the pore density increased. When the calcination temperature reached above 900 °C, the surface microstructure no longer changed significantly. The main component of oyster shell powder is calcium carbonate in the calcite crystal configuration, and it begins to transform into calcium oxide in the limestone configuration under the treatment condition of 800 °C. This transformation has an important impact on the physical and chemical properties of the material. The calcined oyster shell powder will increase its physical adsorption capacity due to its increased surface area and porous structure, thereby increasing its application potential in fields such as environmental remediation. The calcined oyster shell powder has antibacterial and deodorant effects, and also has biocompatibility, which may indicate that the change in crystal configuration is closely related to the antibacterial performance of the material and the biocompatibility of the material.

[0025] Experiments found that introducing nitrogen during the calcination process can increase the conversion rate of calcium oxide; this is mainly because, in some cases, the presence of nitrogen helps to promote the crystal structure transformation of calcium carbonate into calcium oxide, promoting the reaction of calcium carbonate decomposition into calcium oxide and carbon dioxide. At the same time, the decomposed carbon dioxide is more easily removed from the reaction system under the action of the nitrogen gas flow, providing space for further decomposition reactions. And, during the calcination process, introducing nitrogen can reduce the occurrence of side reactions, help to maintain a stable high-temperature environment, and reduce the energy consumption required to reach the calcination temperature.

[0026] During the ultrasonic treatment process, the hydroxyl groups on the surface and inside of oyster shell powder are activated and can interact with the amphoteric compound amino acids. Through ultrasonic waves, L-lysine can be evenly diffused into the inside and surface of oyster shell powder. Since lysine in the modified oyster micropowder is positively charged, it can form electrostatic attraction with negatively charged particles, enabling the particles to adhere to the surface of the water-insoluble carrier. The electrostatic force can enhance the stability between the material and the adsorbed particles; and most environmental microbial cell surfaces in nature are negatively charged, so the microbial affinity can be improved in this way.

[0027] Ultrasonic energy can further disperse oyster shell particles and increase their contact area with the lysine solution, which helps the interaction of active groups. During the ultrasonic treatment process, the hydroxyl groups (-OH) on the oyster shell surface are activated, increasing the surface energy and making these groups more likely to undergo chemical reactions with lysine. In a weakly alkaline environment, the ε-amino group (pKa≈8.95) of lysine is partially protonated (-NH3 + ), while the carboxyl group (-COO - ) remains deprotonated, making the molecule as a whole positively charged and binding to the negatively charged functional groups (such as hydroxyl groups) on the oyster shell surface through electrostatic attraction. Moreover, the amino group of lysine can react with the hydroxyl groups on the surface of oyster shell powder to form covalent bonds (such as ether bonds or ester bonds, etc.), firmly binding lysine to the oyster shell surface. After lysine modification, the charge state of the oyster shell surface changes, and the isoelectric point shifts towards neutral to weakly alkaline, which helps to reduce the electrostatic repulsion with cells.

[0028] The beneficial technical effects of the present invention are as follows:

[0029] The present invention solves the problems of low reaction activity, low calcium oxide conversion rate, low porosity, small specific surface area and pore volume during the calcination process of oyster shell powder, and greatly improves the adsorption performance of the product. The present invention solves the problems of high calcination temperature, long calcination time and high energy consumption during the calcination process of oyster micropowder. By controlling the crystal configuration transformation of oyster micropowder during the calcination process and surface modification treatment, the biocompatibility problem in its application is solved. After mixing oyster shell powder and halloysite, the present invention can prepare modified oyster micropowder with antibacterial and deodorizing effects and excellent adsorption effects. Brief Description of the Drawings

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the following described drawings are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0031] Figure 1SEM images of the products of Example 1 and Comparative Example 1 magnified 3000 times. Among them, (a), (b), and (d) are SEM images of the products of Comparative Example 1 at calcination temperatures of 700 °C, 800 °C, and 1000 °C respectively, and (c) is the SEM image of the product of Example 1.

[0032] Figure 2 Graph of the relationship between the calcination temperature and the calcium oxide conversion rate of the products of Example 1 and Comparative Example 1.

[0033] Figure 3 Graph of the change in the adsorption amount of AOS by the products of Example 1 and Comparative Example 1 under different pH conditions.

[0034] Figure 4 Graph of the change in the phosphate adsorption amount of the product of Example 1.

[0035] Figure 5 Comparison of the adsorption capacities of the product of Example 1 and the modified oyster powder.

[0036] Figure 6 Graph for comparing the antibacterial effects before and after adding the product of Example 1. Among them, (a) is a physical picture of the culture medium without adding the product of Example 1, and (b) is a physical picture of the culture medium after adding the product of Example 1.

[0037] Figure 7 Graph of the antibacterial effects of suspensions with different concentrations in Effect Verification (4).

[0038] Figure 8 XRD patterns of the products of Example 1 and Comparative Examples 1-2. Detailed implementation manners

[0039] Now, various exemplary implementation manners of the present invention will be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, characteristics, and implementation schemes of the present invention. It should be understood that the terms described in the present invention are only used to describe specific implementation manners and are not used to limit the present invention.

[0040] In addition, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.

[0041] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this invention pertains. Although this invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of this invention.

[0042] Regarding "comprising", "including", "having", "containing", etc. used in this invention, they are all open-ended terms, meaning including but not limited to.

[0043] "Room temperature" in this invention, unless otherwise specified, is calculated as 10 - 30 °C.

[0044] All raw materials used in the following examples and comparative examples of this invention are commercially available products.

[0045] Example 1

[0046] A preparation method of halloysite - oyster micropowder:

[0047] 1. Pretreatment of oyster shells: Wash the oyster shells with water, remove residues and contents, dry them in an oven, then use a high-speed crusher to make them into powder, and sieve with a sieve to obtain oyster shell powder with a particle size below 50 mesh.

[0048] 2. Material mixing: Mix the halloysite powder and oyster shell powder that have been crushed to pass through a 30-mesh sieve evenly at a mass ratio of 1:3. Add NaOH and Na2CO3 (each accounting for 3.8%) accounting for 7.6% of the mass of the mixture to the mixture.

[0049] 3. Add MgO: Add MgO to the mixture to obtain an intermediate product (the addition amount of MgO is 10 wt% of the intermediate product).

[0050] 4. Add deionized water: Adjust the pH value of the reaction system to 12.4 - 12.6 by adding deionized water, and carry out fluxing modification for 8 h.

[0051] 5. Drying: Put the prepared material into an electrothermal constant-temperature forced-air drying oven and dry it at 100 °C for 1 h to obtain pretreated powder.

[0052] 6. Calcination treatment: Put the dried mixed material into a square crucible, keep the thickness of the shell powder not exceeding 30 mm, put the square crucible into a high-temperature furnace, control the calcination temperature at 900 °C, and set the calcination time to start timing after the furnace temperature reaches the set temperature. The calcination treatment time is 1 hour. During the calcination process, increase the conversion rate of calcium oxide by introducing nitrogen. Use a high-pressure-resistant nitrogen inlet system, and distribute nitrogen evenly in the furnace through a hollow gypsum tube and an alloy joint. Control the nitrogen flow rate at 500 mL / min, and monitor the temperature change in the furnace to ensure the stability of the calcination temperature.

[0053] 7. Cooling: After the calcination is completed, take it out after the temperature drops to 200 °C and cool it naturally to room temperature.

[0054] 8. Surface modification: Place the cooled oyster shell powder in an excessive sodium carbonate solution (pH value is 13.0) and activate it at 180 °C for 26 h; add the above-activated oyster shell powder to an aqueous solution of L-lysine with a concentration of 13 wt%, and ultrasonically oscillate for 1.5 h (ultrasonic frequency 40 kHz), filter by suction and dry to obtain halloysite-oyster micropowder.

[0055] Comparative Example 1

[0056] The difference from Example 1 is only that the calcination temperatures are modified to 600 °C, 700 °C, 800 °C, and 1000 °C respectively to obtain 5 kinds of halloysite-oyster micropowders.

[0057] Comparative Example 2

[0058] The difference from Example 1 is only that after obtaining the pretreated powder, no calcination treatment is carried out, and it is directly placed in the excessive sodium carbonate solution in Step 8 for activation and subsequent operations to obtain halloysite-oyster micropowder (denoted as without calcination).

[0059] Comparative Example 3

[0060] The difference from Example 1 is only that the addition of halloysite powder is omitted and an equal mass of oyster shell powder is added.

[0061] Comparative Example 4

[0062] The difference from Example 1 is only that the mass ratios of MgO to the intermediate product are modified to 0%, 5%, 15%, and 20% respectively.

[0063] Comparative Example 5

[0064] The difference from Example 1 is only that the calcination atmosphere is modified to air.

[0065] Comparative Example 6

[0066] The difference from Example 1 is only that the step of adding the activated oyster shell powder to the aqueous solution of L-lysine and ultrasonically oscillating in Step 8 is omitted.

[0067] Effect verification

[0068] (1) Verify the influence of SiO2 in halloysite on the calcination and adsorption properties of calcined shells

[0069] The specific surface area and pore structure were measured by BET nitrogen adsorption method (77K). The adsorption performance was evaluated by methylene blue adsorption experiment (initial concentration 50mg / L, 25°C). The initial decomposition temperature (°C) was measured and the reaction enthalpy was calculated. The CaO was measured by acid-base titration method and the CaO conversion rate was calculated.

[0070] The reaction enthalpy, specific surface area, CaO conversion rate, pore volume and methylene blue adsorption amount of halloysite-oyster micropowder in Example 1 and Comparative Example 3 are shown in Table 1 (in Table 1, the three experimental groups are the three measurement results of Example 1, and the three control groups are the three measurement results of Comparative Example 3. There are three samples in each group for different experiments).

[0071] Table 1

[0072]

[0073] It can be seen from Table 1 that the average initial decomposition temperature of the experimental group decreased by 45°C and the reaction enthalpy decreased by about 27 kJ / mol, indicating that SiO2 reduced the activation energy of CaCO3 decomposition by forming a calcium silicate intermediate phase ( Figure 8 The CaSiO3 peak was detected in the XRD of ). The specific surface area and pore volume of the experimental group increased significantly, and the adsorption amount increased by nearly 80%.

[0074] (2) Verify the improvement effect of MgO as a flux on the pore structure of oyster shell calcination

[0075] Taking the products of Example 1 and the products of Comparative Example 4 as experimental samples respectively, the specific surface area and pore structure were measured by BET nitrogen adsorption method (77K). The adsorption performance was evaluated by methylene blue adsorption experiment (initial concentration 50mg / L, 25°C).

[0076] The specific surface area, pore volume, average pore diameter and methylene blue adsorption amount of halloysite-oyster micropowder with different MgO addition amounts in Example 1 and Comparative Example 4 are shown in Table 2 (wherein, groups 1, 2, 4, and 5 are those in Comparative Example 4, and group 3 is Example 1).

[0077] Table 2

[0078]

[0079]

[0080] It can be seen from Table 2 that the average initial decomposition temperature of group 1 is 825°C, while that of group 3 (10% MgO, i.e., Example 1) drops to 755°C, indicating that MgO significantly reduces the pyrolysis energy of CaCO3, and its fluxing effect promotes decomposition by forming a low melting point phase (such as MgCa(CO3)2).

[0081] When the MgO addition amount is 10%, the specific surface area reaches 34.7 m 2 / g (only 15.2 m 2 / g in Group 1), and the pore volume is 0.075 cm 3 / g (only 0.025 cm 3 / g in Group 1), indicating that MgO can form a hierarchical pore structure by inhibiting sintering and promoting pore generation, and the specific surface area and pore volume increase when MgO is added.

[0082] The methylene blue adsorption capacity of the 10% MgO group reaches 82.6 mg / g (only 38.5 mg / g in Group 1), and the adsorption performance is improved by 114%. It can also be seen from this that the performance is the best when the MgO addition amount is 10%; excessive (>15%) leads to too large pore diameters (>14.3 nm), a decrease in specific surface area, and a reduction in adsorption capacity.

[0083] As a flux, MgO: 1. Reduces the pyrolysis energy: promotes the decomposition of CaCO3 and improves the conversion rate of CaO. 2. Optimizes the pore channels: increases the specific surface area and pore volume, and provides more adsorption active sites. The calcination performance of oyster shells is improved, and when the MgO addition amount is 10%, the adsorption performance of the material reaches the peak, verifying its key role in the present invention.

[0084] (3) Research on the role of nitrogen gas during calcination

[0085] The CaO conversion rate, specific surface area, pore volume, and average pore diameter of halloysite-oyster micropowder in Example 1 and Comparative Example 5 are shown in Table 3 (the nitrogen gas group in Table 3 represents Example 1, and the non-nitrogen gas group represents Comparative Example 5).

[0086] Table 3

[0087] Group Conversion rate of CaO (%) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Average pore diameter (nm) Nitrogen group 92.3±2.1 95±8 0.35±0.03 12.5±1.2 Group without nitrogen 68.5±4.7 42±6 0.18±0.02 8.2±1.5

[0088] (Note: The data are the mean ± standard deviation of 15 experiments.)

[0089] It can be seen from Table 3 that there is a difference in the CaO conversion rate, and the conversion rate of the nitrogen gas group is significantly higher than that of the non-nitrogen gas group (92.3% and 68.5%).

[0090] The reason for this is that as an inert gas, nitrogen effectively discharges CO2 and promotes the forward progress of the CaCO3 decomposition reaction (CaCO3 → CaO + CO2↑); while the CO2 partial pressure in the air is relatively high, which inhibits the decomposition. Secondly, the specific surface area (95 m 2 / g) and pore volume (0.35 cm 3 / g) of the nitrogen gas group are both better than those of the non-nitrogen gas group (42 m 2 / g, 0.18 cm 3 / g). It is speculated that the reason is that under a nitrogen atmosphere, the growth of CaO crystals is restricted, forming a porous nanostructure; while without nitrogen, the reverse reaction of CO2 causes partial recarbonation of CaO, resulting in densification of the structure.

[0091] From a statistical perspective, through a t-test, the p-value of the two groups of data is <0.001, indicating that nitrogen has a significant effect on improving the product performance.

[0092] The final conclusion is that nitrogen significantly promotes the decomposition efficiency of CaCO3 in oyster shells and optimizes the pore structure of the product by reducing the partial pressure of CO2, thereby improving the adsorption performance. Under the condition of no nitrogen, the activity and structural characteristics of the product both decrease significantly, verifying the key role of nitrogen in the calcination process.

[0093] (4) Verification of the improvement of the material by L-lysine modification

[0094] Surface charge analysis was carried out using a Zeta potential analyzer (measuring the surface charge of the material). Using negatively charged methylene blue (10 mg / L) and congo red (10 mg / L) as adsorbates, the adsorption amounts were compared under the conditions of conventional adsorption (without ion interference) and the addition of 0.5 M NaCl (shielding the electrostatic force). By selecting negatively charged Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis), the adsorption rate of the material to microorganisms was determined by the colony counting method to conduct the microbial affinity experiment.

[0095] The Zeta potential, adsorption amount without NaCl, adsorption amount with 0.5 M NaCl, adsorption rate of Escherichia coli, and adsorption rate of Bacillus subtilis of halloysite-oyster micropowder in Example 1 and Comparative Example 6 are shown in Table 4 (the three experimental groups in Table 4 are the results of three measurements in Example 1, and the three control groups are the results of three measurements in Comparative Example 6. Three samples were used in each group for different experiments).

[0096] Table 4

[0097]

[0098] As can be seen from Table 4, the Zeta potential increased from an average of -15.4 mV in the control group to an average of +28.6 mV in the experimental group, confirming that L-lysine imparts a positive charge to the material surface. The adsorption amount of methylene blue by the experimental group without NaCl reached 82.6 mg / g (only 38.2 mg / g in the control group), a 116% increase. After adding NaCl, the adsorption amount of the experimental group decreased to 44.6 mg / g (a 46% decrease), while that of the control group only decreased by 5%, indicating that the electrostatic force is the main adsorption mechanism.

[0099] As can be seen from Table 4, the adsorption rates of the experimental group for Escherichia coli and Bacillus subtilis reached 78.4% and 73.5% respectively (only 21.5% and 18.3% for the control group), proving that the positively charged surface significantly enhances the microbial binding ability through electrostatic attraction.

[0100] The reason is that the microbial cell wall (containing carboxyl and phosphate groups) is negatively charged and tightly binds to the positively charged surface of the modified material through Coulomb force, improving biocompatibility.

[0101] The conclusion is:

[0102] 1. L-lysine modification significantly enhances the adsorption ability of the material for negatively charged particles through surface positive electrification, and the adsorption stability depends on electrostatic force (the adsorption amount decreases significantly after NaCl shielding).

[0103] 2. The adsorption rate of the modified material for negatively charged microorganisms is increased by 3 - 4 times, verifying its core mechanism of improving biocompatibility through electrostatic interaction.

[0104] This modification strategy can be widely applied in the fields of environmental remediation (pollutant adsorption) and biomaterials (microbial carriers).

[0105] (5) Microscopic morphology analysis

[0106] Figure 1 It is the SEM image of the products of Example 1 and Comparative Example 1 magnified 3000 times. Among them, (a), (b), and (d) are the SEM images of the products in Comparative Example 1 at calcination temperatures of 700 °C, 800 °C, and 1000 °C respectively, and (c) is the SEM image of the product of Example 1.

[0107] From Figure 1 it can be seen that when the calcination temperature is 700 °C, the fine structure of oyster shell powder is planar; when the calcination temperature reaches 800 °C, its planar structure disappears, and the particles form a multi-porous configuration with a flocculent structure, and its pores are between 10 - 20 microns; as the temperature increases to 900 °C, the flocculent structure of oyster shell powder increases, and at the same time the pore size decreases; when the calcination temperature reaches 1000 °C, its pore size is about 5 microns.

[0108] The specific surface area, pore volume, and pore diameter of halloysite - oyster micropowder at different calcination temperatures in Example 1 and Comparative Examples 1 - 2 are shown in Table 5 (the sample with a calcination temperature of 0 °C in Table 5 represents the product of Comparative Example 2).

[0109] Table 5

[0110] Calcination temperature / °C <![CDATA[Specific surface area / (m 2 ·g -1 )]]> <![CDATA[Pore volume / (cm 3 ·g -1 )]]> Pore diameter / μm Mesoporous content / % 0 4.911 0.044 14.055 42.30 700 1.653 0.014 11.411 48.18 800 3.392 0.023 10.348 50.75 900 3.925 0.066 6.374 65.33 1000 1.583 0.015 5.406 55.12

[0111] (6) Adsorption capacity test

[0112] Taking the product of Example 1 and the products of Comparative Example 1 at calcination temperatures of 800 °C and 1000 °C as experimental samples, the adsorption test of alginate oligosaccharides (AOS) was carried out.

[0113] The experimental steps are as follows:

[0114] 1. Preparation of AOS solution: Prepare an aqueous solution of alginate oligosaccharides (AOS) with an initial concentration of 0.5 g / L.

[0115] 2. pH adjustment: Adjust the pH value of the solution to the target range (0, 3, 7, 11, 14) with 0.1 M HCl / NaOH, a total of 5 key points.

[0116] 3. Adsorption experiment:

[0117] Take 50 mL of AOS solution in a conical flask and add 0.05 g of adsorbent (i.e., 1 g / L addition ratio).

[0118] Oscillate at 150 rpm for 2 hours at 25 °C (pre-experiment shows that the adsorption equilibrium is reached at this time).

[0119] 4. Centrifugal separation: Take the supernatant and centrifuge (8000 rpm, 10 min), and measure the remaining AOS concentration.

[0120] 5. Concentration determination: Use ultraviolet spectrophotometry (detection wavelength 210 nm) or sulfuric acid-phenol method (measure the absorbance at 490 nm after color development), and calculate the concentration through the standard curve.

[0121] The test results are as Figure 3 shown.

[0122] Figure 3 It is a graph showing the change in the adsorption amount of AOS by the products of Example 1 and Comparative Example 1 under different pH conditions.

[0123] The purpose of testing the AOS adsorption effect in the present invention is not only to evaluate the adsorption performance, but more importantly, to expand the application fields: by improving the adsorption ability and biocompatibility of oyster shell powder, it can be used in drug carriers (such as AOS controlled release systems), adsorbing heavy metals / organic pollutants in water bodies, and embedding and slow releasing functional components in the food industry, etc.

[0124] Through the above experimental design, the influence of different calcination temperatures on the adsorption performance of the material can be systematically evaluated, and at the same time, the optimal process parameters can be determined (the calcination at 900 °C combined with alkaline activation treatment has the best effect). The test results support the application potential of oyster shell powder in the fields of drug delivery, environmental adsorption, etc.

[0125] Using the product of Example 1 as an experimental sample, phosphate adsorption tests were carried out. The test method was as follows: At 25 °C, an aqueous phosphate solution with a concentration of 2.5 g / L was prepared (the pH value of the solution was 12, and the phosphate type was sodium phosphate).

[0126] The test results are as Figure 4 shown.

[0127] Figure 4 It is a graph showing the change in the phosphate adsorption capacity of the product of Example 1.

[0128] The phosphate adsorption kinetics of the samples before and after modification was studied, and the test results are shown in Figure 5.

[0129] Figure 5 It is a comparison of the adsorption capacities of the product of Example 1 and unmodified oyster shell powder (the oyster shell powder with a particle size below 50 mesh in Step 1, without other treatments).

[0130] From Figure 5 it can be seen that the adsorption process of phosphate on oyster shell powder conforms to pseudo-second-order adsorption, indicating that the adsorption process is not a simple physical adsorption, but also there is chemical adsorption, and chemical adsorption may be the rate-limiting step in the adsorption process.

[0131] (7) Bacteriostatic rate experiment

[0132] Take 5 mL of Escherichia coli suspension with a colony count of 10 4 CFU / mL in a test tube. Immediately take 100 μL of the supernatant and spread it evenly on an agar solid medium, and place it in a constant temperature and humidity incubator at 37 °C for 24 h (for the physical picture of the medium at this time, see Figure 6 (a)), and record the colony count at this time (denoted as N0); Take 5 mL of Escherichia coli suspension with a colony count of 10 4 CFU / mL in a test tube, add 1.0 g of halloysite-oyster micropowder of Example 1, and then place the test tube in a constant temperature and humidity shaker and shake it at 37 °C for 1 h. Then take 100 μL of the supernatant and spread it evenly on an agar solid medium, and place it in a constant temperature and humidity incubator at 37 °C for 24 h (for the physical picture of the medium at this time, see Figure 6 (b)), and record the colony count at this time (denoted as N). Calculate the bacteriostatic rate according to the following formula.

[0133] Bacteriostatic rate (%) = (N0 - N) / N0 * 100%

[0134] After measurement, after adding the halloysite-oyster micropowder of Example 1, N0 = 1000, N = 1, and the bacteriostatic rate reached 99.9%.

[0135] Figure 6It is a comparison chart of the antibacterial effects before and after adding the product of Example 1. Among them, (a) is a physical picture of the culture medium without adding the product of Example 1, and (b) is a physical picture of the culture medium after adding the product of Example 1.

[0136] As Figure 6 shown, there is basically no growth of bacterial colonies in the culture medium after adding the modified oyster micropowder, which is significantly different from the culture medium without adding the modified oyster micropowder.

[0137] Conduct an antibacterial zone width experiment:

[0138] Incubate at 37 °C for 24 hours to ensure the full diffusion of the antibacterial substance. During this period, maintain the humidity in the incubator to prevent the culture medium from cracking. Through the above condition control, the antibacterial effect of oyster shell micropowder (the product of Example 1) on Escherichia coli can be systematically evaluated, and its growth inhibition mechanism through diffusion can be verified. The test results are shown in Table 6 and Figure 7 as shown.

[0139] Table 6

[0140]

[0141] As can be seen from Table 6, compared with the control group, all filter papers loaded with different concentrations of oyster micropowder produced antibacterial zones. And as the suspension concentration increases, the width of the antibacterial zone also increases. This indicates that the oyster micropowder in the filter paper loaded with the modified oyster micropowder can diffuse into the culture medium through diffusion, inhibit the growth of Escherichia coli, and form an antibacterial zone.

[0142] Figure 7 It is the antibacterial effect diagram of suspensions with different concentrations in Effect Verification (4).

[0143] (8) X-ray diffraction

[0144] Since in a high-temperature environment, SiO2 in halloysite will also react with calcium carbonate to form calcium silicate (CaSiO3), thus affecting the proportion of CaO in the product; and the adsorption capacity of calcium silicate is worse than that of calcium oxide. Therefore, studying the proportion of calcium silicate in the modified oyster micropowder at different calcination temperatures is of positive significance for the characterization of the product performance of the present invention.

[0145] Figure 8 It is the XRD diagram of the products of Example 1 and Comparative Examples 1-2.

[0146] XRD analysis shows that the main components of the material before calcination are CaCO3 and a small amount of MgO and SiO2. CaO was found in the material calcined at 700 °C, indicating that partial thermal decomposition of CaCO3 occurred. When the temperature reached 800 °C, the peak of CaO was significantly enhanced compared to that at 700 °C, and FTIR showed that the characteristic peak of CaCO3 weakened, indicating that a large amount of CaCO3 thermally decomposed into CaO at this temperature. XRD analysis at 900 °C found that CaSiO3 began to appear in the material and the content of CaO reached its peak. When the temperature reached 1000 °C, the infrared spectrum of the material changed completely, indicating that an obvious solid-phase reaction occurred under this condition, and new substances such as Nepheline, Gehlenite, and CaSiO3 became the main components of the material. Therefore, in the present invention, the calcination temperature is set at 900 °C. Although a small amount of CaSiO3 is produced at this time, it does not affect the performance and effect of the final product.

[0147] The embodiments described above are only descriptions of the preferred modes of the present invention and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various deformations and improvements made by those of ordinary skill in the art to the technical solutions of the present invention shall fall within the protection scope determined by the claims of the present invention.

Claims

1. A preparation method of surface-modified halloysite-oyster micropowder, characterized in that, It includes the following steps: Mix halloysite powder and oyster shell powder to obtain a mixed powder; Mix the mixed powder with MgO in alkaline solution 1 to obtain an intermediate product, perform flux modification to obtain a pretreated powder, and calcine to obtain a calcined powder; Place the calcined powder in alkaline solution 2 for activation, and then place it in an L-lysine aqueous solution for reaction to obtain halloysite-oyster micropowder.

2. The preparation method according to claim 1, characterized in that, The halloysite powder is halloysite powder ground to pass through a 30-mesh sieve, and the oyster shell powder is oyster shell powder ground to pass through a 50-mesh sieve.

3. The preparation method according to claim 1, characterized in that, The mass ratio of the halloysite powder to the oyster shell powder is 1:

3.

4. The preparation method according to claim 1, wherein The pH value of alkaline solution 1 is 12.4 - 12.6; the addition amount of MgO is 10 wt% of the intermediate product; the time for flux modification is 8 h.

5. The preparation method according to claim 1, characterized in that, The temperature of the calcination is 900 °C, and the time is 1 h; the atmosphere of the calcination is a nitrogen atmosphere, and the nitrogen flow rate is 500 mL / min.

6. The preparation method according to claim 1, characterized in that, The pH value of alkaline solution 2 is 12.8 - 13.2; the activation temperature is 160 - 200 °C, and the time is 24 - 28 h.

7. The preparation method according to claim 1, characterized in that, The concentration of the L-lysine aqueous solution is 10 - 15 wt%; the reaction time is 1 - 2 h, the reaction is carried out under ultrasonic conditions, and the ultrasonic frequency is 40 kHz.

8. Surface-modified halloysite-oyster micropowder obtained by the preparation method according to any one of claims 1 - 7.

9. Application of the surface-modified halloysite-oyster micropowder according to claim 8 in the field of adsorption materials.